The Utilization Implementation of High Sea According to Sea Convention - Ong Argo Victoria; Saleh Raed Shatat (Jurnal Daulat Hukum, 2021)
The purpose of this research is to find out how the implementation of the use of forms of freedom on the high seas according to the 1982 Law of the Sea Convention (UNCLOS 1982) and how the exceptions to freedom on the high seas according to the 1982 Law of the Sea Convention (UNCLOS 1982). The research method used in this research is using normative legal research methods and it can be concluded that the regulation regarding the high seas is contained in Part VII Article 86 to Article 120 of the 1982 Sea Law Convention to take advantage of the high seas. State freedoms on the high seas are freedoms in accordance with article 87, namely freedom of navigation, flight, laying submarine cables and pipelines, freedom to build artificial islands and other installations, freedom to fish, and freedom to conduct scientific research. Every given freedom can be used by every country but every country is obliged to maintain and utilize the high seas for peaceful purposes for the survival of human life. In addition to providing freedom to use the high seas, the 1982 Law of the Sea Convention provides exceptions to this freedom. Where every country is free to use the high seas but is not allowed to take illegal actions or violate the law, both national law and international law, which in its application are often violated by countries in the world. There are several exceptions to the freedom of the high seas such as the prohibition of slavery, piracy, trafficking in narcotic drugs and psychotropic substances, instant pursuit, illicit broadcasting, and pollution of the marine environment. So every country, both coastal and non-coastal countries, is required to cooperate in eradicating all forms of abuse of freedom on the high seas.